SISTEM PAKAR UNTUK MENENTUKAN KELUARGA BERENCANA ALAMI MENGGUNAKAN METODE FUZZY TSUKAMOTO - Noviyanti P; Yuliana Yuliana (Politeknik Bisnis Indonesia, 2021)
Family Planning (KB) according to the BKKBN is a program that has a function to help married couples in the process of delaying the birth of their first child (postponing), spacing the birth of their next child (spacing) or limiting the number of children the husband wants. wife. In general, married couples do family planning using hormonal contraception. Several studies explain that the use of hormonal contraception has side effects that can be experienced by women, such as experiencing headaches, weight gain, menstrual disorders, changes in vaginal fluids, vaginal pain, mood changes, and changes in sexual desire. The side effects given by using hormonal contraception can be a consideration for married couples in determining how to do family planning. One of the family planning programs that can be said to be safe from side effects such as those caused by the use of hormonal contraception is KBA (Natural Family Planning). This study aims to help married couples determine a safe schedule for sexual intercourse with a guide that can be seen in the system based on input from the user, so this research requires the help of an expert or expert who understands the KBA program, such as a midwife or nurse. Obstetricians. This study uses the Fuzzy Tsukamoto method by utilizing variables that affect the KBA program and determining the degree of membership, so that output will be obtained based on input from the user. Based on the tests that have been carried out, an accuracy of 100% is obtained based on 10 test data.